Answer:
see explanation
Step-by-step explanation:
Given
f(x) = 2x + 1
(a)
To evaluate f(2) substitute x = 2 into f(x), that is
f(2) = 2(2) + 1 = 4 + 1 = 5
(b)
let y = f(x) and rearrange making x the subject
y = 2x + 1 ( subtract 1 from both sides )
y - 1 = 2x ( divide both sides by 2 )
[tex]\frac{y-1}{2}[/tex] = x
change y back into terms of x and x = [tex]f^{-1}[/tex] (x) , thus
[tex]f^{-1}[/tex] (x ) = [tex]\frac{x-1}{2}[/tex]
(c)
To evaluate the inverse function substitute x = 7, that is
[tex]f^{-1}[/tex] (7) = [tex]\frac{7-1}{2}[/tex] = [tex]\frac{6}{2}[/tex] = 3